Media Pembelajaran Syariat Islam Pada Anak Usia Dini Berbasis Android - Ghifron Akhiru Syahroni; Shinta Esabella; Eri Sasmita Susanto (Bulletin of Information Technology (BIT), 2023)
Limited facilities and low learning media infrastructure are two of the causes of the low quality of Indonesian education. This applies to children at TPQ Al-Ikhsan Dusun Boak Dalam, where learning methods still use books and whiteboards, which are relatively boring for children, and some material is still very difficult to understand. This disrupts the learning process. Then a solution is needed to answer this problem, namely by having an Android-based learning media application that includes Islamic law material for children. This study aims to develop an Android-based application that is specifically designed for learning media for Islamic law in early childhood at TPQ Al-Ikhsan Dusun Boak Dalam so that it makes it easier for children to understand learning material. The resultstugas of this study are in the form of an Android-based prototype of Islamic Shari'a learning media applications in early childhood that can help children understand learning material.